Developing quality evaluation instrument for Islamic Senior High School - Muh Shodiq; S. Suyata; Sutrisna Wibawa (Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
This research aims to develop concept of the quality of education in Islamic Senior High School and know the validity and reliability of the factors that affect the development of quality indicators in Islamic Senior High School. Development of the procedures in this research included a needs analysis, product development, product test, and implementation/ dissemination. A sample of this research was Islamic Senior High School 1 Surakarta and Islamic Senior High School 1 Purwodadi, which were determined by a purposive random sampling. Data analysis techniques used was Confirmatory Factor Analysis (CFA), Lisrel version 8.54, and descriptive qualitative analysis. The results of the study showed that the development of quality indicator for Islamic Senior High School includes six criteria namely, the role of school principals, management of Islamic Senior High School, educators and Staffs, Students, facilities and infrastructures and the role of the community. It has met the indicators fit models, the Chi-Square value is 152.07, p 0.05, and RMSEA is 0.068. The advantages of this Islamic Senior High School Quality Evaluation Instrument are namely comprehensive holistic approach, easy, not depending on the specific lessons conducted by educators. It can be used to map the various aspects of the education in Islamic school that need to be repaired; it is open to further developed) Islamic school quality evaluation instrument can be used as a school self-evaluation; it can be used effectively by schools without interrupting the learning process; it supports school accreditation and quality guarantee, and it is also independent.